Isolation of lactoferrin from whey by dye-affinity chromatography with Yellow HE-4R attached to chitosan mini-spheres - Baieli, María Fernanda (2014)
Novel integrated chromatographic methods need to be developed for specific, low-cost protein purification from raw materials. Here, a process for bovine lactoferrin (Lf) isolation from sweet whey was developed using cross-linked chitosan mini-spheres with immobilised Yellow HE-4R dye as a low-cost ligand. The maximum adsorption capacity was between 51.14 and 58.28 mg Lf g−1 matrix. In addition, the mini-spheres adsorbed around 95% of the Lf present in the sweet whey and eluted more than 80% of the adsorbed Lf. A yield of 77% with purity greater than 90% was achieved in only one purification step. The purification process was efficient for three consecutive cycles without regeneration steps.